The Effect of Trigonella foemun-gracum Extract on the Fungi that Isolated from the Libraries Door (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
The study  included the isolation and diagnosis of the fungi from the door  of the laboratories  (microbology  ,technical biology )in the technical  institute of Babylon from the medical department.  The study appeared many  of the different kinds of fungi: Absidia sp,Candidia sp, Aspergillus  sp,Penicillum  sp. The  rate of appearance of the type of the fungi  in  microbology laboratory  is the higher than the technical biology laboratory other.The rate of appearance of the fungi   Aspergillus niger was 36.8% and Absidia ,Penicililum  was 21.05% , Candida sp  was 15.7 %  , Aspergillus flavus  5.2% while  in the technical biology the fungi Aspergillus  terrus was 15.7% and the fungi  Penicililum sp,Candida  albcans, Apergillus niger was 20%  ,  Absidia sp ,Alternaria sp was  10%.The study  showed  the influence  of the heating  water  extract  hot watering  extract  the race track in the concentration which is used( 10,20,30, 40) mg /ml on some of fungi. The rate of reduction is appeared 100% of the  fungi Candida  albicans  in the concentration (30,40) mg/ml and  the  range of the diameter colony of the yeast Candida  albicans in the concentration 30 mg/ml the (1)sanatamtar. While the fungi Aspergillus  niger in the concentration (10,20)mg/ml is not given any resistance toward the extract.